Practical guidelines for the management of adverse events of the T cell engager bispecific tebentafusp - Hassel, Jessica C.; Berking, Carola; Forschner, Andrea; Gebhardt, Christoffer; Heinzerling, Lucie; Meier, Friedegund; Ochsenreither, Sebastian; Siveke, Jens; Hauschild, Axel; Schadendorf, Dirk (European journal of cancer, 2023)
Tebentafusp is a new T cell receptor bispecific fusion protein and the first approved treatment option for human leucocyte antigen-A*02:01 (HLA-A*02:01) metastatic uveal melanoma, with a proven benefit in overall survival versus the investigator’s choice. As a first-in-class therapeutic option, this Immune mobilising monoclonal T cell receptor Against Cancer (ImmTAC) is associated with a new adverse event (AE) profile. Based on clinical experience, a national expert group discussed recommendations for tebentafusp treatment, focusing on AE management. Further topics included prerequisites for initiating tebentafusp treatment, appropriate treatment setting, and patient selection criteria. To provide guidance for treating physicians, the resulting recommendations are summarised including a model standard operating procedure for AE management. Patients in good clinical condition and with a low tumour burden are good candidates for tebentafusp treatment, particularly if treated as early as possible after the diagnosis of metastatic disease. The safety profile of tebentafusp is manageable and includes two major pathologies: cytokine release syndrome (CRS) and skin-related events. Postdose monitoring should thus focus on pyrexia and hypotension as the first symptoms of cytokine release. To minimise the risk of hypotension associated with CRS, patients should receive intravenous fluids before starting treatment. The monitoring of liver values is crucial, as patients may experience an increase in transaminases, which can even manifest as tumour lysis syndrome.